2006
DOI: 10.1105/tpc.106.044958
|View full text |Cite
|
Sign up to set email alerts
|

Two Arabidopsis Threonine Aldolases Are Nonredundant and Compete with Threonine Deaminase for a Common Substrate Pool

Abstract: Amino acids are not only fundamental protein constituents but also serve as precursors for many essential plant metabolites. Although amino acid biosynthetic pathways in plants have been identified, pathway regulation, catabolism, and downstream metabolite partitioning remain relatively uninvestigated. Conversion of Thr to Gly and acetaldehyde by Thr aldolase (EC 4.1.2.5) was only recently shown to play a role in plant amino acid metabolism. Whereas one Arabidopsis thaliana Thr aldolase (THA1) is expressed pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 52 publications
4
72
0
1
Order By: Relevance
“…First, a growing body of evidence points to major roles of amino acid catabolism and interconversion in regulating levels of six of the nine free essential amino acids (Ile, Leu, Lys, Met, Thr, and Val) in seeds of a variety of plants (Karchi et al, 1994;Zhu and Galili, 2003;Jander et al, 2004;Joshi et al, 2006;Lee et al, 2008;Gu et al, 2010;Lu et al, 2011;Angelovici et al, 2013). These results indicate that modifying catabolism has the potential to improve the nutritional quality of crop seeds and vegetative tissues.…”
Section: Broader Implicationsmentioning
confidence: 93%
“…First, a growing body of evidence points to major roles of amino acid catabolism and interconversion in regulating levels of six of the nine free essential amino acids (Ile, Leu, Lys, Met, Thr, and Val) in seeds of a variety of plants (Karchi et al, 1994;Zhu and Galili, 2003;Jander et al, 2004;Joshi et al, 2006;Lee et al, 2008;Gu et al, 2010;Lu et al, 2011;Angelovici et al, 2013). These results indicate that modifying catabolism has the potential to improve the nutritional quality of crop seeds and vegetative tissues.…”
Section: Broader Implicationsmentioning
confidence: 93%
“…In vitro enzyme assays, as well as complementation of an S. cerevisiae gly1 shm1 shm2 mutant, which is a glycine auxotroph (McNeil et al, 1994;Monschau et al, 1997), showed that two A. thaliana genes, At1g08630 (THA1) and At3g04520 (THA2) encode threonine aldolases (Jander et al, 2004;Joshi et al, 2006). Whereas tha1 mutations greatly increase seed threonine content (Jander et al, 2004), tha2 mutations cause a lethal albino phenotype (Joshi et al, 2006). Rescue of a tha1 tha2 double mutant by overexpression of threonine deaminase (At3g10050) shows that glycine formation from threonine is not essential for A. thaliana, and that the lethal effects of tha2 mutations may result from the accumulation of excess threonine.…”
Section: Threonine Catabolismmentioning
confidence: 99%
“…For amino acid analysis, samples were analyzed using a Waters 2790 HPLC system as described previously (Joshi et al, 2006), with a minor modification whereby the ratio of tissue to extraction buffer was 1:3. For measuring leaf DIMBOA-Glc content, sample extraction and HPLC analysis were performed as described previously (Mijares et al, 2013).…”
Section: Targeted and Untargeted Metabolite Assaysmentioning
confidence: 99%